Myocardial infarction with a preserved ejection fraction—the impaired function of the cardio-renal baroreflex - Pickny, Lisa; Hindermann, Martin; Ditting, Tilmann; Hilgers, Karl F.; Linz, Peter; Ott, Christian; Schmieder, Roland E.; Schiffer, Mario; Amann, Kerstin; Veelken, Roland; Rodionova, Kristina (Frontiers in Physiology, 2023)
Introduction: In experimental myocardial infarction with reduced ejection fraction causing overt congestive heart failure the control of renal sympathetic nerve activity by the cardio-renal baroreflex was impaired. Afferent vagal nerve activity under these experimental conditions had a lower frequency at saturation than controls. Hence, we wanted to test the hypothesis that after myocardial infarction with still preserved ejection fraction the cardiac afferent nerve pathway is also already impaired by investigating respective first neurons in the nodose ganglion. Material & Methods: Myocardial infarction induced by coronary artery ligature. After 21 days, nodose ganglion neurons with cardiac afferents from rats with myocardial infarction were cultured. Current clamp used to characterize neurons as “tonic”, i.e., sustained action potential (AP) firing or “phasic”, i.e., <5 APs upon current injection. Cardiac ejection fraction measured with echocardiography; renal sympathetic nerve activity (RSNA) recorded to evaluate the sensitivity of the cardiopulmonary baroreflex. Renal and cardiac histology for inflammation and fibrosis marker. Results: 192 neurons were investigated. In rats after myocardial infarction, the number of neurons with a tonic response pattern increased compared to controls (infarction vs. control: 78.6 % vs. 48.5%; z-test, *P<0.05) with augmented production of APs (23.7+/−2.86 vs. 15.5+/−1.86 APs/600ms; mean+/-SEM, t-test, *P<0.05). The baseline activity of RSNA was subtly increased and its control by the cardiopulmonary baroreflex impaired following myocardial infarction: The fibrosis marker collagen I augmented in the renal interstitium. Discussion: Already after myocardial infarction with still preserved ejection fraction, a complex impairment of the afferent limb of the cardio-renal baroreflex caused dysregulation of renal sympathetic nerve activity with signs of renal fibrosis.